Weight loss practices, perceptions, and eating disorder symptoms among Chinese male adolescent combat sports athletes - Meng, Fanjie; Zhang, Zhao; Xu, Kai; Lvu, Mengde; Zhong, Yuming (Frontiers in Nutrition, 2026)
ObjectivesThis study investigated weight loss (WL) practices, perceptions, and eating disorder (ED) symptoms among Chinese male adolescent combat sport (CS) athletes.MethodsA convenience sampling approach was employed. An adapted Rapid WL Questionnaire and Eating Disorder Examination Questionnaire-8 (EDE-Q8) were used, with 525 and 285 valid responses obtained, respectively. Only participants who had engaged in WL were invited to complete the EDE-Q8.ResultsFifty-seven percent of participants intentionally engaged in WL practices. The mean habitual WL was 7.2% of body mass (BM), and the highest WL was 9.6% of BM. Significant differences were observed in the age at which WL practices began, highest WL%, and habitual WL% across competitive levels (p = 0.024, p = 0.009, p = 0.010) and sports discipline (p = 0.003, p = 0.009, p = 0.010). Habitual WL% also differed by allocated WL duration (p = 0.010). Participants predominantly allocated ≥15 days before the weigh-in for WL (67%). Coaches (78%) were most frequently identified as the primary source of WL guidance. The primary reason reported for engaging in WL was to compete against lighter opponents to increase the likelihood of winning (71%). Most participants perceived that WL had no impact on health (49%), is beneficial to performance (41%), and does not lead to unfair competition (80%). No significant differences in sports discipline, competitive level, or WL practices were observed across athletes with different perceptions. Eighteen percent of participants were classified as exhibiting ED symptoms. Athletes with and without ED symptoms did not differ significantly in habitual WL%. Restraint and global ED scores differed significantly among athletes who allocated different habitual durations for WL (p = 0.036, p = 0.005). Additionally, habitual WL% was positively correlated with eating concern score (p = 0.018).ConclusionThe magnitude of WL among Chinese male adolescent CS athletes was greater than that reported in previous studies. Most athletes engaged in longer-term WL, allocating ≥15 days, primarily through increased exercise and the use of plastic suits. The higher ED scores were associated with higher habitual WL% and longer allocated WL duration.